2018
DOI: 10.1111/ajt.14876
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric heart transplantation across a positive crossmatch: First year results from the CTOTC-04 multi-institutional study

Abstract: Sensitization is common in pediatric heart transplant candidates and waitlist mortality is high. Transplantation across a positive crossmatch may reduce wait time, but is considered high risk. We prospectively recruited consecutive candidates at eight North American centers. At transplantation, subjects were categorized as nonsensitized or sensitized (presence of ≥1 HLA antibody with MFI ≥1000 using single antigen beads). Sensitized subjects were further classified as complement-dependent cytotoxicity crossmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 25 publications
0
36
2
Order By: Relevance
“…18 More recently, Webber et al reported a higher incidence of a composite outcome (death, re-transplant, and haemodynamically significant rejection) in recipients with a positive crossmatch heart transplant (18.2%). 19 This observation when compared to the composite outcome of 10.7% in the negative XM group was not statistically significant probably due to the small sample size. These results give hope to the feasibility of transplant across a positive crossmatch for select patients, especially when a better defined antibody-mediated rejection treatment regimen can be formulated as several small studies in the adult renal transplant population have reported promising results in the treatment of antibody-mediated rejection with eculizumab.…”
Section: Discussionmentioning
confidence: 81%
“…18 More recently, Webber et al reported a higher incidence of a composite outcome (death, re-transplant, and haemodynamically significant rejection) in recipients with a positive crossmatch heart transplant (18.2%). 19 This observation when compared to the composite outcome of 10.7% in the negative XM group was not statistically significant probably due to the small sample size. These results give hope to the feasibility of transplant across a positive crossmatch for select patients, especially when a better defined antibody-mediated rejection treatment regimen can be formulated as several small studies in the adult renal transplant population have reported promising results in the treatment of antibody-mediated rejection with eculizumab.…”
Section: Discussionmentioning
confidence: 81%
“…The cardiac consortium of the NIAID/NIH-sponsored Clinical Trials in Organ Transplantation in Children (CTOTC) program (www.ctotc.org) was developed to explore the impact of alloantibodies on pre- and post-transplant outcomes in pediatric heart candidates, with a focus on the management of the highly sensitized candidate including those with a positive donor-specific cytotoxicity crossmatch. 17,18 Study design, candidate sensitization status, risk factors for sensitization and primary outcomes from CTOTC-04 are described elsewhere in this volume. 17,18 CTOTC-04 also provides a unique opportunity to study the clinical importance of ndDSA in the first year after pediatric heart transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Study design, candidate sensitization status, risk factors for sensitization and primary outcomes from CTOTC-04 are described elsewhere in this volume. 17,18 CTOTC-04 also provides a unique opportunity to study the clinical importance of ndDSA in the first year after pediatric heart transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to differing strategies in the approach to highly sensitized patients, including protocols for antibody depletion following transplantation across a positive XM as well as efforts aimed toward desensitization in the pretransplant period . Recent data from the CTOTC‐04 multi‐institutional study demonstrated that patients transplanted across a positive XM have a greater incidence of cellular and antibody‐mediated rejection, but no difference in the cumulative end‐point of death, retransplantation, or rejection with hemodynamic compromise at 1‐year follow‐up . Data from our survey clearly demonstrate that there is no consensus in the approach to patients who are highly sensitized.…”
Section: Discussionmentioning
confidence: 86%
“…[36][37][38] Recent data from the CTOTC-04 multi-institutional study demonstrated that patients transplanted across a positive XM have a greater incidence of cellular and antibody-mediated rejection, but no difference in the cumulative end-point of death, retransplantation, or rejection with hemodynamic compromise at 1-year follow-up. 39 Data from our survey clearly demonstrate that there is no consensus in the approach to patients who are highly sensitized. There was near perfect equipoise in the utilization of prospective crossmatching and in the willingness to transplant across a positive virtual XM, irrespective of desensitization strategy.…”
Section: Criteria Impacting Acceptance Of a Marginal Donormentioning
confidence: 86%